Disposable and flexible smart electronic tapes for long-term biopotential monitoring - Jiuwei Gao; Mingwei Hu; Hao Sun; Yuanyuan Wang; Yuan Wei; Weiwei Li; Lu Zheng; Manzhang Xu; Qianbo Lu; Zhiyuan Liu; Hui Yang; Yongtian Wang; et al. (npj Flexible Electronics)
Abstract Long-term biopotential acquisition is of great significance for the early detection and timely treatment of various diseases. Currently, the standard silver/silver chloride (Ag/AgCl) gel electrodes may cause skin irritation when worn for a long time. Repeating the use of electrodes on different individuals can lead to the risk of cross-infection. Here, we propose a smart electronic tape (SET) to acquire biopotentials, in the form of a dry single-sided tape made from a combination of an ultra-stretchable conductive pattern on substrates with different functions. The high stability and durability of the patterned conductors provide accurate and timely acquisition of biopotentials, such as electrocardiograph (ECG) and electromyography (EMG). The strong adhesive behavior of the tape as well as the low-cost manufacturing process allow convenient and long-term wearing in a disposable manner. We anticipate the SET will pioneer next-gen wearable electronics for applications like disease prevention, health monitoring, and human–computer interaction.